Bepridil monotherapy failed to prevent coronary vasospasm in a Brugada syndrome patient. Issue 8 (18th August 2022) - Kazatani, Takuro; Higaki, Akinori; Tanaka, Yuta; Kawada, Yoshitaka; Hiasa, Go; Yamada, Tadakatsu; Okayama, Hideki
ABSTRACT: Coronary vasospasm sometimes coexists with Brugada syndrome (BrS) and is reportedly associated with poor prognosis. Although calcium channel blockers are considered first-line drugs to prevent coronary vasospasm, they also have the potential to induce ST elevation and ventricular fibrillation (VF) in BrS. Therefore, the optimal medication for such a complicated case is still underdetermined. We report a male patient who presented with VF due to BrS, which was later found to have coexisted with coronary vasospasm. He was treated with low-dose bepridil expecting both its anti-arrhythmic and vasodilatory effects, but a later acetylcholine provocation test showed no suppression of vasospasm. Based on these results, we decided to add nitrates to the medication. This case report illustrates that drug selection needs caution in BrS when complicated with vasospastic angina and that bepridil monotherapy may not be sufficient to suppress coronary vasospasm in such cases.